Rituximab-associated hypogammaglobulinemia in children with idiopathic nephrotic syndrome: Results of an ESPN survey - (:unkn) unknown (My University, 2023)
Background: There is paucity of information on rituximab-associated hypogammaglobulinemia (HGG) and its potential infectious consequences in children treated for idiopathic nephrotic syndrome (INS). Methods: A survey was distributed by the European Society Pediatric Nephrology to its members. It addressed the screening and management practices of pediatric nephrology units for recognizing and treating RTX-associated HGG and its morbidity and mortality. Eighty-four centers which had treated an overall 1328 INS children with RTX responded. Results: The majority of centers administered several courses of RTX and continued concomitant immunosuppressive therapy. Sixty-five percent of centers routinely screened children for HGG prior to RTX infusion, 59% during, and 52% following RTX treatment. Forty-seven percent had observed HGG prior to RTX administration, 61% during and 47% >9 months following treatment in 121, 210, and 128 subjects respectively. Thirty-three severe infections were reported among the cohort of 1328 RTX-treated subjects, of whom 3 children died. HGG had been recognized in 30/33 (80%) of them. Conclusions: HGG in steroid-dependent/frequently relapsing nephrotic syndrome (SDNS/FRNS) children is probably multifactorial and can be observed prior to RTX administration in children with SDNS/FRNS. Persistent HGG lasting >9 months from RTX infusion is not uncommon and may increase the risk of severe infections in this cohort. We advocate for the obligatory screening for HGG in children with SDNS/FRNS prior to, during, and following RTX treatment. Further research is necessary to identify risk factors for developing both HGG and severe infections before recommendations are made for its optimal management. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; Children; Hypogammaglobulinemia; Nephrotic syndrome; Rituximab